2010
DOI: 10.1007/s11060-010-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgical treatment planning of AVM following embolization with Onyx: possible dosage error in treatment planning can be averted

Abstract: Treatment of arteriovenous malformations (AVM) of the brain is challenging due to the size and location of the nidus-proper and its proximity to the cerebrovascular circulation. Recent advances in catheter techniques and new embolization materials such as Onyx (a liquid agent that is less adhesive and slowly polymerizing) have increased the probability of achieving obliteration. When planning radiosurgical cases following such embolization, however, one must be cognizant of the distortions introduced by this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…Potential dosimetric inaccuracies have been suggested with onyx embolization material and the effect of other embolization agents has not been fully understood (16) . In our study four AV M patients had undergone partial glue embolization, and the dose shift with the convolution algorithm in these cases was comparable to subjects who had not had endovascular treatment before GKR.…”
Section: Discussionmentioning
confidence: 61%
“…Potential dosimetric inaccuracies have been suggested with onyx embolization material and the effect of other embolization agents has not been fully understood (16) . In our study four AV M patients had undergone partial glue embolization, and the dose shift with the convolution algorithm in these cases was comparable to subjects who had not had endovascular treatment before GKR.…”
Section: Discussionmentioning
confidence: 61%
“…9 Shtraus et al found that the measured attenuation of Onyx placed in a bottle was around 3% higher than the attenuation of water. 58 The biomaterial properties of Onyx appear to be reflected in the current clinical study. The difference in obliteration rate was not statistically significant between patients who did not undergo prior embolization and those that did, when they had comparable AVM volume, grading, and radiation dose.…”
Section: Discussionmentioning
confidence: 88%
“…9,35 The possible dosage attenuation caused by previous embolic materials can be averted with Onyx embolization. 58 The present study aims to evaluate the outcome of SRS treatment of AVMs after Onyx embolization. These cases were matched to a cohort of patients who underwent SRS as an upfront treatment.…”
mentioning
confidence: 99%
“…Wilczek et al 10 tested the dose perturbation induced by different stents in brachytherapy and noticed that the shielding effect exists and depends on the strut thickness and mesh attenuation rather than on the atomic number of the metal. Shtraus et al 11 found that the measured attenuation of Onyx placed in a bottle was 3% higher than the attenuation of water. Light ion beams can also be used in radiosurgery, with clinically and radiobiologically interesting results, especially for large BAVMs.…”
Section: Discussionmentioning
confidence: 98%